Co-crystallisation of cytosine with 1, 10-phenanthroline: computational screening and experimental realisation1. Issue 37 (7th October 2015) - Hoxha, Kreshnik; Case, David H.; Day, Graeme M.; Prior, Timothy J.
<x xml:space="preserve">Abstract</x> Crystal structure prediction calculations applied to co-crystals of 1, 10-phenanthroline and nucleobases (A, T, C, G) show that only cytosine is expected to form a 1 : 1 co-crystal. Experiments provide verification for this result although the observed co-crystal crystallises with Z′ = 2, not Z′ = 1.